Potential health risks of long-term e-cigarette use - Eric A Klomparens; Yuchuan Ding (Wolters Kluwer Medknow Publications, 2019)
E-cigarettes are becoming increasingly popular in recent years, especially among adolescents. Many healthcare professionals are unsure of what health consequences can be expected after long-term use of e-cigarettes. This review focuses on the currently published data of long-term e-cigarette vapor exposure in cells, animals, and humans. Most research suggests that e-cigarettes are not harmless. Increased oxidative stress from free radicals and systemic inflammation occur after weeks or months of exposure. E-cigarette vapor contains multiple known human carcinogens which are found in the serum of users, and DNA damage is seen in exposed animals. Pulmonary changes seen after months of exposure in mice are reminiscent of chronic obstructive pulmonary disease (COPD), and human users report increased respiratory symptoms. Cardiovascular disease risk is also likely, with e-cigarette use leading to multiple pathophysiological changes and possibly associated with an increased risk of myocardial infarction. Limitations of the current research are discussed, including the retrospective nature of most human data to date. A call for large, longitudinal prospective studies is deemed necessary to better understand the causal role of long-term e-cigarette use in chronic disease formation.